Detection and Phylogenetic Characterization of a Novel Herpesvirus in Sooty Terns Onychoprion fuscatus - Sebastiano, Manrico; Canestrelli, Daniele; Bisconti, Roberta; Lavergne, Anne; Pineau, Kévin; Chastel, Olivier; Lacoste, Vincent; Costantini, David (Frontiers in Veterinary Science, 2020)
Since 2005, we have recorded annual episodes of alphaherpesvirus outbreaks in chicks of magnificent frigatebird Fregata magnificens on the Ile du Grand Connétable Nature Reserve in French Guiana. In 2009, we found sooty terns, Onychoprion fuscatus, that live sympatrically with frigatebirds, with visible clinical signs of a potential viral infection. To determine if the symptoms observed in sooty terns could be associated with an alphaherpesvirus previously identified in frigatebirds, we carried out molecular screening of samples collected from seven individuals. We identified and characterized a novel viral sequence from five birds. BLAST searches, pairwise nucleotide and amino acid sequence comparisons, as well as phylogenetic analyses confirmed that the sequence belonged to the Herpesviridae family, of the Alphaherpesvirinae subfamily. We observed that it clustered with strains isolated from Podargidae (Caprimulgiformes), Columbiformes, and Falconiformes, but was distinct from the frigatebird herpesvirus. We have tentatively named it Onychoprion fuscatus alphaherpesvirus 1, (OfusAHV1). These two sequences, although found syntopic on the Ile du Grand Connétable, belong to two distinct alphaherpesvirus strains. Thus, the clinical symptoms showed by sooty terns do not likely result from a cross-species transmission event. Future work is needed to better characterize the virus and to investigate herpesvirus prevalence in healthy, free-ranging sooty terns, and to assess the impact of the virus on population viability.